Question
Asked Sep 9, 2019
6 views

Simplify the expressions below.

(a) tan(cos−1 x)
 
 


(b) sin(tan−1 x)
check_circle

Expert Answer

Step 1

(a)

help_outline

Image Transcriptionclose

Let, => COS a X a COS X We know that sin2acos2a 1 sin2a 1 -cos2a => tV1-cos2a sin a = (cos a x) sin a = tan(cos x) tan a so, sin a COs a _ = + X

fullscreen
Step 2

Answer:

help_outline

Image Transcriptionclose

1 - x2 tan(cos x) X

fullscreen
Step 3

(b)

...
help_outline

Image Transcriptionclose

1 X Let, tan a= x => a tan We know that sec2a 1tan2a sec2a tan2a = 1 => V1 tan2a => sec a = (tan a x) V1+x2 sec a= 1 1 (cosa => COS a= V1x2 sec a sin(tan x)sin a -1 so, = tan a cos a X

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Calculus

Other

Related Calculus Q&A

Find answers to questions asked by student like you
Show more Q&A
add
question_answer

Q: Evaluate the integral to find the area of the shaded region Set up and evaluate the integral for the...

A: Firstly, we find the points at which the curve meet the x-axis , by setting y=0, and solve for x

question_answer

Q: Number 21

A: Calculation:Compute the given integral using Substitution method.Let u = v3, then du = 3v2dv.Obtain ...

question_answer

Q: I am 16 years old and dropped of high school to get a ged and go to college. These dudes put me in a...

A: Local extrema’s in a graph, are the points where, a tangent at that point will be parallel to x-axis...

question_answer

Q: Find the limits as x - oo and as x » -o. y f(x) (2 - x)(1 + x)2(1 - x)4 lim f(x) 1 X X co lim f(x) U...

A: Given,

question_answer

Q: calculate the derivative of the function. Then find the value of the derivative as specified.

A: First write the expression using exponent.

question_answer

Q: Taylor Expansion In class we used several results from Taylor expansion. (a) Prove In(1 -e) - n n-1 ...

A: (a)Given statement is: The Taylor expansion for ln (1 – x) is given by:Plugging x = e in the above s...

question_answer

Q: Use the graph of f(x) to answer the following

A: We will refer to the given plot of f(x) to determine the various values of limit asked in the questi...

question_answer

Q: Please answer all of the questions. Elaborate and make clear the last graph because that is the one ...

A: a.  Since the equation of the curve is y=cosπx, the slope of the secant line PQ  between the points,...

question_answer

Q: Does continuity of f imply continuity of f? Let 94. 1 g(x)=1 if x 0 if x< 0. -1 a. Write a formula f...

A: Hello there! As you have uploaded a question with multiple sub-parts, we will answer only the first ...